Omalizumab usage off-label - review of the knowledge obtained over the last 10 years from research in specific diseases - Fahim, Knieszko; Franaszek, Jakub; Herchi, Nadia; Jabrzyk, Martyna; Jarczyńska, Patrycja; Kijowski, Wojciech; Klusek, Mateusz; Michalak, Karolina; Przybył, Maciej (Quality in Sport, 2026)
Introduction: Omalizumab, a humanized monoclonal antibody binding to human Immunoglobulin E (IgE), limits free IgE triggering allergic reactions. Officially indicated for allergic asthma, chronic rhinosinusitis with nasal polyps, and chronic spontaneous urticaria, its off-label potential is gaining clinical interest. This spans common conditions like atopic dermatitis to rare diseases like systemic mastocytosis. Aim of the study: To analyze knowledge from the last decade (2016–2026) on the off-label clinical efficacy of omalizumab in atopic dermatitis, IgE-mediated food allergy, latex allergy, systemic mastocytosis, and allergic bronchopulmonary aspergillosis (ABPA). Materials and methods: A literature review of the PubMed database (2016–March 2026) was conducted using standardized search strings. Findings were supplemented by clinical guidelines and official drug characteristics from specialized medical textbooks and registries. Conclusions: Omalizumab shows promising yet variable efficacy as an off-label therapy across IgE-mediated and inflammatory disorders. In food and latex allergies, it is a highly effective adjunct to oral immunotherapy, enabling safer, rapid desensitization. In cystic fibrosis patients with refractory ABPA, it yields consistent pulmonary (FEV1) and serological improvements. For atopic dermatitis, omalizumab significantly reduces severity in pediatric populations but is ineffective in adults with massively elevated IgE. In systemic mastocytosis, it prevents anaphylaxis in highly symptomatic patients, though trial results remain mixed. Ultimately, while offering substantial therapeutic potential, successful off-label application requires highly individualized, disease-specific dosing protocols rather than standard asthma nomograms.